Investigating the role and applicability of patient versions of guidelines in oncology and deriving recommendations for the development, dissemination and implementation of patient versions in Germany: protocol for multiphase study. Issue 3 (16th March 2022) - Becker, Monika; Bühn, Stefanie; Meyer, Nora; Blödt, Susanne; Carl, Günther; Follmann, Markus; Frenz, Stefanie; Langer, Thomas; Nothacker, Monika; Santesso, Nancy; Schaefer, Corinna; Pieper, Dawid
Abstract : Introduction: The German Guideline Program in Oncology (GGPO) has published patient versions of clinical practice guidelines for more than 10 years. However, a systematic evaluation of these is lacking. The project aims to investigate the role and applicability of patient versions by considering the perspectives of experts, patients and healthcare providers to derive recommendations for the development, dissemination and implementation of patient versions in Germany. Methods and analysis: The project comprises two main modules. In module 1, we will first obtain information on methods and approaches for the development, dissemination and implementation of patient versions by conducting systematic searches in Medline and screening the websites of guideline organisations. We will include any articles, such as methodological or empirical reports, published in German or English since 2000, that address methodological aspects related to patient versions. Further, we will conduct 20 interviews with experts from international and German organisations who are involved in the development of patient versions. In module 2, we will first conduct interviews to explore patients and healthcare providers' perceptions of patient versions of the GGPO. For the group of patients and the group of healthcare providers, we aim to conduct 25 interviews each. Second, we will conduct focus groups, separately for breast, prostate and colon cancer. The recruitment of participants for the interviews and focus groups will primarily be done through a previous survey about patient versions in oncology. The results will be used to derive recommendations for enhancing the development, dissemination and implementation of patient versions by involving the relevant stakeholder groups. Ethics and dissemination: Ethical approval for the qualitative parts of the project was given by the Ethics Committee of Witten/Herdecke University (number 160/2021). Participants will be required to provide informed consent. The project findings will be published in peer-reviewed journals and presented at scientific conferences.